Acquisition of the Rights to the Post-Liquidation Assets of the Cooperative - Stepnowska, Marta (PRAWO i WIĘŹ, 2026)
In cooperative law, a crucial issue is the admissibility or inadmissibility of distributing the cooperative's assets among its members at the liquidation stage. Any assets remaining after liquidation are allocated for the purposes specified in the resolution of the last general meeting. This meeting may decide that the remaining assets are to be distributed, either wholly or in part, amongst the cooperative's members, or possibly amongst former members or heirs. It is important to determine both the timing of the distribution and those entitled to the liquidation surplus.